Colonial Subjects and Citizens in the French Internal Resistance, 1940-1944. Issue 1 (1st March 2019) - Broch, Ludivine
Abstract : In recent decades historians have done a lot to reveal the social and political diversity of the people who participated in the French Resistance. But little has been said about non-white resisters who were among the 200, 000 men and women from the colonies living in the French metropole during the Occupation. This article shows that many of them were entangled in the Resistance as early as the summer of 1940 and that they became involved in the most political and violent forms of defiance. Resistance, however, was not a "natural" decision for many of the colonial workers or prisoners, whose daily struggles could bring them into tension with the Free French as well as Vichy. So, if this study aims to rectify misconceptions of the Resistance as an entirely Eurocentric affair, it also probes the complicated relationship between colonial subjects and the metropole during the war.